2022
DOI: 10.1007/s12144-021-02576-9
|View full text |Cite
|
Sign up to set email alerts
|

Psychological maltreatment, coping flexibility, and death obsession during the COVID-19 pandemic: A multi-mediation analysis

Abstract: Recent psychological studies have reported that child maltreatment is a common issue during the COVID-19 pandemic, with negative factor leading to greater risk of occurrence of mental health problems. However, the relationship between psychological maltreatment and psychological factors is complex. Understanding the factors, which may help to provide interventions, is a critical step for mental health providers. This study aims to examine the relationships between psychological maltreatment, coping flexibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Mengo et al in their cross-sectional study found that coping strategies mediated the relationship between abuse and mental health issues [23]. A recent study also confirmed that coping strategies mediated the relationship between childhood maltreatment and suicidal ideation [24].…”
Section: Introductionmentioning
confidence: 89%
“…Mengo et al in their cross-sectional study found that coping strategies mediated the relationship between abuse and mental health issues [23]. A recent study also confirmed that coping strategies mediated the relationship between childhood maltreatment and suicidal ideation [24].…”
Section: Introductionmentioning
confidence: 89%
“…Individuals use stress coping schemas to assess risk resources or to choose ways to cope with stress. Stress coping schemas are essentially a stress coping model based on ideas from positive psychology and cross-cultural psychology, emphasizing the role of cultural schemas and the diversity of patterns used to cope with stress (Bodenmann & Cina, 2006;Kılınç et al, 2023). Van Wijk-Herbrink et al (2018) have proposed a new definition of creative and culture-focused coping.…”
Section: Introduction Regnancy As a Stage Of Female Identity Formationmentioning
confidence: 99%